Evaluation the correlation between Inulin and Cystatin C with kidney function tests and GFR in patients with renal disorders - Nawar Mohsin Abd-alaziz; Wasan Nazhan Hussein (Tikrit Journal of Pure Science, 2020)
Background: Kidneys are important organs in the human body because of their great importance in assisting the body to remove waste products that resulting from food metabolism through renal filtration of blood plasma from unwanted substances and excreted through diuresis and recover substances that body needs to the blood, relative effectiveness of the kidney can be estimated by measuring the efficiency of glomerular filteration rate (GRF), represented by amount of inulin filtrate into renal tubules for a specified period of time, any difference in normal value indicates the presence of a disorder in the kidney, which affects on performance of its functions and occurrence of imbalance in internal environment of the body, and leads to disrupting functions of other parts of the body, measuring rate of renal filtration is one of the best ways to know function of the kidneys and diagnose various kidney diseases and prevent their development. Materials and Methods : The study included measuring rate of inulin clearance in the blood plasma, and estimating level of cystatin C and a number of biochemical variables in serum and evaluation the effect of body mass index BMI. 50 sample was collected from patients with chronic renal failure, and 50 sample of patients with diabetic nephropathy and 50 sample as control group. Results: The results indicate that a significant decrease in the rate of inulin clearance in plasma and serum albumin, with a significant increase in level of serum cystatin C, glucose, urea and creatinine, and a non significant differences in level of serum uric acid in patients with chronic renal failure and diabetic nephropathy as compared to control group.